2019
DOI: 10.1186/s40981-019-0292-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of postoperative nausea and vomiting is not increased by combination of low concentration sevoflurane and propofol compared with propofol alone in patients undergoing laparoscopic gynecological surgery

Abstract: Background: The incidence of postoperative nausea and vomiting (PONV) is higher in patients receiving volatile anesthetics than those receiving total intravenous anesthesia (TIVA) with propofol. However, it is unclear whether its incidence is increased when a low concentration of sevoflurane is used in combination with propofol. Methods: This prospective, randomized, controlled trial enrolled women undergoing laparoscopic gynecological surgery. Patients were randomly assigned to receive general anesthesia eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…25 The mechanism by which propofol may modulate the risk of PONV is not well understood. 11,26,27 Propofol infusions could have a direct antiemetic effect, could decrease the dose of volatile anesthetics needed to maintain anesthesia, 11,13,14 or both.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 The mechanism by which propofol may modulate the risk of PONV is not well understood. 11,26,27 Propofol infusions could have a direct antiemetic effect, could decrease the dose of volatile anesthetics needed to maintain anesthesia, 11,13,14 or both.…”
Section: Discussionmentioning
confidence: 99%
“…For example, use of propofol with a low sevoflurane concentration (0.8%) does not increase the incidence of PONV compared with total intravenous anesthesia with propofol. 11 In another study, the PONV rate was lower in patients receiving a combination of sevoflurane and propofol versus sevoflurane alone. 12 Adding a propofol infusion to volatile anesthesia theoretically provides 2 benefits: 1) since volatile agents are associated with PONV and use of propofol may allow for decreasing the concentration of volatile agents, [13][14][15] the rate of PONV may be expected to be reduced; and 2) by simultaneously using lower doses of 2 anesthetics with different elimination pathways, recovery room stay may be shortened.…”
mentioning
confidence: 94%
“…During laparoscopic surgeries in the Trendelenburg position, increased ONSD as a surrogate parameter of ICP is highly correlated with the occurrence of PONV [28]. Other factors, including female and anesthetic technique, increase the risk of PONV [29]. In this study, two patients from the Sevoflurane group experienced PONV even though they were administered antiemetics, but these occurrences were not statistically significant.…”
Section: Discussionmentioning
confidence: 54%
“…Firstly, although the power analysis indicated that the number of patients who were required in the present study was sufficient, the population size was relatively small and this was a singlecenter study. This may be an underlying reason explaining statistically non-significant differences in postoperative adverse reactions between the PRD and PR groups and the lower PONV observed (1/30 patients, 3.3%) compared with previous reports (20-50%) (4,31,32). Secondly, the enrolled patients were relatively young and whether the conclusion is similar in an older population requires further validation.…”
Section: Discussionmentioning
confidence: 76%